Вплив Фредеріка Кіслера на формування світогляду просторового мистецтва сучасності - Баланюк, Юліана; Balaniuk, Juliana (Видавництво Львівської політехніки, 2020)
В статті висвітлюється вплив Ф. Кізлера на формування єдиного пластичного мистецького простору на противагу поширеним в той час ідеям “чистої архітектури”. Основний внесок Кізлера в теорію дизайну полягав в тому, що він поставив на перше місце не предмет і не групу предметів, а процес взаємодії різних компонентів один з одним і з мінливою реальністю. Винайдений ним термін “корреалізм” використовувався для дослідження тривалої взаємодії між людиною і навколишнім середовищем, як техногенним, так і природнім. Таке дослідження базувалося, з одного боку, на експериментальному, а з іншого – на інтуїтивному осягненні процесів. Переосмислення Ф. Кізлером традиційних підходів до мистецтва стало поштовхом для формування нового просторового мистецтва.

The main idea of the article is the research of Frederick Kiesler impact on formation of contemporary plastic arts instead of ideas of “clear architecture” which were common at that time. Kiesler hadn’t been satisfied with the modern functional architecture of his time – the white painted box. In his extreme architectural vision, Kiesler hoped to perform this same ultimate cleansing – to regenerate and liberate humanity to start all over, free again. His main idea in arts was the cooperation between parts of different arts, Kiesler used his own term “correalizm” to show the continuing collaboration between human and surrounding both technical and nature. Reconsideration of traditional ways by Frederick Kiesler gave a new life to formulation of new spatial art. Twentieth-century art are filled with contradictions and still is not researched enough. But those art was a crucial point for birth the new genres, which impressed by diversity and paradoxes. This new genres of arts first of all were based on synthesis of their forms. That period was also formed a new generation of artists, who affected on development of all sphere of arts by their works, and Kiesler was among them. Despite the word famous, the genius of Frederick Kiesler and his creation isn’t researched enough in foreign and domestic publishing. Among published works about Kiesler in Ukraine belong to Kyiv and Lviv architecture schools: Proskuriakov V., Proskuriakov O., Bilenkova S., Korotun I., Nykyrsa M. and others. Also the last interesting research works were demonstrated during the International architecture online conference “The influence of futuristic ideas of F. Kiesler on the development of architectural practice and theory in Ukraine and the world”. The initiators of this conference were Chernivtsy National University and National University “Lviv polytechnic”. The aim of this article is demonstrate some of Kiesler’s periods of life and creation, which are characterized by innovation approaches and synthesis of arts, correalizm and influenced on creation of contemporary spatial art. Kiesler also fell short in his own ambitions to educate students to think about the work they were producing. His work marks a prescient moment in the history of modern design. His laboratory research engaged scientific study of dynamic bodily habits and sensorial affects to support shifting biopolitical structures aimed at advancing capitalist markets and evolving control societies. Although Kiesler’s body of work would later suggest alternative and more-resistive liberatory applications, his efforts to produce responsive systems designed to modulate to the qualities and intensities of dynamic bodies-in-motion most often seemed to facilitate and promote a society of unconsciously motivated actions. In a contemporary context where architecture research laboratories are continuing to emerge internationally – with ever-greater claims toward innovative study of continuous forms, responsive systems, and sensational affects – Kiesler’s challenges and failures as an educator are even more poignant today. Regardless of one’s own values or institutional biases, to teach students to unwittingly speculate, experiment, and produce is simply not enough. As educators, we are also responsible for teaching students to think about what they are learning to do.
Frederick Kiesler impact on formation of contemporary plastic arts worldview
Keywords: просторове мистецтво; пластичне мистецтво; сюрреалізм; сучасний дизайн; Фрідріх Кізлер; корреалізм; spatial art; plastic art; surrealism; modern design; Friedrich Kiesler; correalism; 72.03(477) (045)